Deconstructing 3D structured materials by modern ultramicrotomy for multimodal imaging and volume analysis across length scales [research data and source code] - Wacker, Irene; Curticean, Ernest Ronald; Ryklin, Daniel; Weidinger, Britta; Mayer, Frederik; Huang, Li-Yu; Hoffmann, Julian; Islam, Monsur; Coelln, Nadine von; Schmitt, Tanja; Huck, Christian; Tegeder, Petra; et al. (Universität, 2023)
Based on the rapid advances in additive manufacturing, micro-patterned heterostructures of soft materials have become available that need to be characterized down to the nanoscale. Advanced function-structure relationships are designed by direct 3D structuring of the object and - in the future - fine control over material functionality in 3D will produce complex functional objects. To control their design, fabrication and final structure, morphological and spectroscopical imaging in 3D at nanometer resolution are critically required. With examples of carbon-based objects, it is demonstrated how serial ultramicrotomy, that is, cutting a large number of successive ultrathin sections, can be utilized to gain access to the interior of 3D objects. Array tomography, hierarchical imaging and correlative light and electron microscopy can bridge length scales over several orders of magnitude and provide multimodal information of the sample's inner structure. Morphology data derived from scanning electron microscopy are correlated with spectroscopy in analytical transmission electron microscopy and probe microscopy at nanometer resolution, using TEM-electron energy loss spectroscopy and infrared-scanning-near-field microscopy. The correlation of different imaging modalities and spectroscopy of carbon-based materials in 3D provides a powerful toolbox of complementary techniques for understanding emerging functions from nanoscopic structuring.